2002
DOI: 10.1002/jbm.a.10436
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy and imaging of the dentin–enamel junction in human third molars

Abstract: A 351-nm laser excitation source was used to perform autofluorescence microscopy of dentin, enamel, and the dentin-enamel junction (DEJ) to obtain information regarding their morphology and spectral characteristics. The emission spectra of these calcified dental tissues were different from one another, and this enabled the DEJ to be imaged and dimensionalized. The DEJ displayed sharp and clearly delineated borders at both its enamel and dentin margins. The dentinal tubules and the enamel prisms appeared to ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…Fong et al (2000) observed the polished and etched junction with AFM and found an interpenetrating structure with width comparable to the functional width they found with nanoindentation (about 20 lm). Optical spectroscopic imaging ($1 lm spatial resolution) of polished human third molars revealed widths from 7-15 lm with a median of 10 lm (Gallagher et al, 2003). The results reported here are, therefore, consistent with the literature, especially when one considers the differences in imaging methods and the uncertainties from study to study of what is actually being measured.…”
Section: Discussionsupporting
confidence: 92%
“…Fong et al (2000) observed the polished and etched junction with AFM and found an interpenetrating structure with width comparable to the functional width they found with nanoindentation (about 20 lm). Optical spectroscopic imaging ($1 lm spatial resolution) of polished human third molars revealed widths from 7-15 lm with a median of 10 lm (Gallagher et al, 2003). The results reported here are, therefore, consistent with the literature, especially when one considers the differences in imaging methods and the uncertainties from study to study of what is actually being measured.…”
Section: Discussionsupporting
confidence: 92%
“…Developing and mature DEJs have been studied by immunohistochemical staining (Goldberg et al, 2002), transmission and scanning electron microscopy (SEM) (Lin et al, 1993;TenCate, 1978), autofluorescence (Gallagher et al, 2003), and Raman spectroscopy (Shulze et al, 2004). The DEJ fracture properties have been tested by a wide range of techniques (Dong and Ruse, 2002;Rasmussen, 1984;Urabe et al, 2000), and the mechanical properties have been investigated using AFM and nanoindentation (Fong et al, 2000;Marshall et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There is common agreement that the DEJ is not an interface in mathematical sense but rather an extended transition region. Different reports on the DEJ width show variation in intra-tooth location [20][21][22][23]. Enamel, the outmost part of human tooth crowns and the hardest tissue in the human body, is composed of 92-96 wt% inorganic and approximately 4 wt% of organic substance [24].…”
Section: Introductionmentioning
confidence: 99%